Comparison of Cardiac Size in Posteroanterior Chest X-Ray and Echocardiography - Agustining Rahayu; Bachtiar Murtala; Sri Asriyani; Andi Alfian Zainuddin; Muzakkir Muzakkir; Nikmatia Latief (Majalah Kedokteran Sriwijaya, 2019)
Cardiac size is important to determine the presence of cardiac enlargement caused by left ventricular enlargement or right ventricular enlargement. Although echocardiography is considered to be the gold standard for cardiac enlargement, its availability is limited, expensive and requires trained experts. The posteroanterior (PA) chest X-ray (CXR) is the most common imaging used as a reliable alternative. The aim of this study was to compare cardiac size using cardiothoracic ratio (CTR) and transverse left cardiothoracic ratio (TL-CTR) in PA chest X-ray and echocardiography. This cross- sectional study involved 88 inclusion sample, aged 20-60 years. On the basis of provisional clinical diagnosis, the patients were divided three groups, consist of: (i) Group with normal cardiac size, (ii) Group with left ventricular enlargement (LVE) dan (iii) Group with right ventricular enlargement (RVE). All patients underwent PA CXR and M-Mode echocardiography examinations. The results of the two modalities were compared. CTR and TL-CTR, transverse diameter (TD) and transverse left (TL) in PA chest X-ray showed a strong positive correlation with total ventricular dimension (TVD) and left ventricular internal dimension (LVID) in echocardiography. CTR, TL-CTR, TD and TL in the PA chest X-ray are very good indicators for TVD and LVID in echocardiography. Chest X-ray is a reliable alternative for the diagnosis of cardiomegaly/cardiac enlargement in the absence of echocardiography.